2005
DOI: 10.1007/s00540-004-0285-x
|View full text |Cite
|
Sign up to set email alerts
|

Halothane modulates NMDA and non-NMDA excitatory synaptic transmission in rat cortical neurons

Abstract: These results show that halothane causes decrease of excitatory synaptic activity, with NMDA EPSCs being more sensitive than non-NMDA EPSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In recent years, many in vitro studies have shown that the mechanism of anesthesia may involve cell membranes, multiple receptors, ion channels, and neurotransmitters [10][11][12]. The N-methyl-D-aspartate (NMDA) receptor is an important excitatory amino acid receptor in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many in vitro studies have shown that the mechanism of anesthesia may involve cell membranes, multiple receptors, ion channels, and neurotransmitters [10][11][12]. The N-methyl-D-aspartate (NMDA) receptor is an important excitatory amino acid receptor in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…This could represent a higher baseline sympathetic tone. With the interplay of disease and anesthesia on the NMDA receptor, potential exists for the exacerbation of neurologic symptoms or paroxysmal sympathetic hyperreactivity (PSH) 5–8 . None of our patients experienced arrhythmias nor hemodynamic lability while under anesthesia.…”
Section: Discussionmentioning
confidence: 89%
“…The NMDA receptor is also a common target for anesthetic agents. Patients with anti‐NMDA receptor encephalitis could potentially have unique anesthetic consequences 5–8 . The anesthetic implications of this disease process are unknown, especially for pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of action of halogenated agents are complex and not fully understood. Isoflurane and halothane are known to enhance GABA A synaptic inhibition (Antkowiak 1999), and to block NMDA receptors (Ming et al 2002, Kitamura et al 2005). These mechanisms are shared by drugs that had no effect in any of the cases.…”
Section: Methodsmentioning
confidence: 99%